INFORMATION TECHNOLOGIES OF THE STATISTICAL DATA ANALYSIS WITHIN THE SYSTEM OF HIGHER PSYCHOLOGICAL EDUCATION - Svetlana V. Smirnova; Tatyana A. Makarchuk (Статистика и экономика)
The features of using information technologies within applied statisticians in psychology are considered in the article. Requirements to statistical preparation of psychology students in the conditions of information society are analyzed.